In response to 'Six critical questions about smart spezialisation'. Issue 10 (3rd October 2019) - Foray, Dominique
ABSTRACT: This paper has been written as a response to « Six critical questions about smart specialization » by R. Hassink and H. Gong. The paper starts with a reminder of what has not changed in terms of the basic principles and raison d'être of smart specialization. Then it proceeds to identifying what we have learned since 2014 and on this basis it will address the six critical questions posed by Robert and Huiven.